Birth Companionship as a Non-Pharmacological Strategy to Reduce Maternal Anxiety and Enhance Perceived Support and Safety During Childbirth - Nila Trisna Yulianti; Rika Handayani; Rahmat Haji Saeni; Fajar Akbar (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Birth companionship is globally recognized as an effective non-pharmacological approach to improving maternal psychological well-being during labor, yet evidence from Indonesian urban settings remains limited. This study evaluated mothers’ perceptions of birth companions and examined changes in anxiety levels before and after an intervention consisting of antenatal education and continuous companionship during labor. A quasi-experimental one-group pretest–posttest design was conducted involving 30 primigravida mothers in Balikpapan, Indonesia. Data were collected using closed-ended nominal questionnaires and analyzed with the McNemar test. Significant improvements were observed in several maternal perception indicators, including feeling calmer (p = 0.000), emotionally supported (p = 0.004), physically assisted (p = 0.016), helped in communicating with health workers (p = 0.008), and safe and comfortable during labor (p = 0.031). Maternal anxiety levels also decreased significantly across key indicators, including fear of childbirth (p = 0.016), negative thoughts (p = 0.016), restlessness while waiting for labor (p = 0.001), and feelings of helplessness (p = 0.016). These findings indicate that antenatal education combined with continuous birth companionship is effective in enhancing perceived support and safety while reducing pre-delivery anxiety. However, because this study used a one-group pretest–posttest design without a comparison group, the generalizability and causal interpretation of the findings remain limited. Further research employing controlled or randomized designs is recommended to strengthen causal inference and expand applicability.